2019
DOI: 10.1123/pes.2018-0115
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Flexibility in Children With Duchenne Muscular Dystrophy: Effects on Functional Performance

Abstract: Objective: To investigate the effects of lower limb flexibility on the functional performance of children with Duchenne muscular dystrophy. Methods: Thirty children, whose functional levels were at 1 or 2 according to the Brooke Lower Extremity Functional Classification Scale, were included in this study. The flexibilities of the hamstrings, hip flexors, tensor fascia latae, and gastrocnemius muscles were evaluated in the children’s dominant lower limbs. The children’s functional performance was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…The study found that the proposed MSR angular analysis can negate the effects of anthropometric characteristics without changing testing procedures and testing devices. Since children with Duchenne muscular dystrophy [ 20 ] and with a history of plagiocephaly [ 21 ] have been reported to have poor flexibility, it can be considered that such an MSR angular analysis might have good application prospects in children with typical or atypical development.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the proposed MSR angular analysis can negate the effects of anthropometric characteristics without changing testing procedures and testing devices. Since children with Duchenne muscular dystrophy [ 20 ] and with a history of plagiocephaly [ 21 ] have been reported to have poor flexibility, it can be considered that such an MSR angular analysis might have good application prospects in children with typical or atypical development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the relationship between ankle limitation and functional capacity in children with DMD are limited. Kaya (Kaya et al, 2014) and Akkurt (Akkurt, Gürbüz, Karaduman, & Yilmaz, 2019) used 6MWT to study the relationship between ankle limitation and walking function in children with DMD. Both studies reported significant relationships between ankle limitation and 6MWT.…”
Section: Discussionmentioning
confidence: 99%
“…Sporcularda yapılan bir çalışmada ise daha az hamstring esnekliği olan sporcuların %30 daha fazla yaralanma riskine sahip olduğu ve performanslarının daha düşük olduğu bulunmuştur [25]. DMD'de de hamstring esnekliğinin fonksiyonel performans üzerine etkisi araştırılmış ve önemli ölçüde etkilediği bildirilmiştir [9].…”
Section: İstatikselunclassified
“…Esneklik ise tam eklem hareket açıklığına ulaşabilme kapasitesidir. Nöromusküler hastalıklarda daha çok kısalıklar üzerinde durulmaktadır [6,8], ancak esneklik ile özellikle de hamstring ve sırasıyla gastrokinemius, kalça fleksörleri ve TFL esnekliği ile performans arasındaki kuvvetli ilişki önceki çalışmada gösterilmiştir [9]. Literatürde DMD'de esneklik ile performans arasındaki ilişki gösterilmesine rağmen esneklik ile ambulasyon arasındaki ilişkiyi gösteren çalışma bulunmamaktadır.…”
unclassified